21st Century English Language Education: Revisiting Idealism and Realism in Enhancing Pedagogical Skills - Khan, Aslam Khan Bin Samash (English Language and Literature International Conference (ELLiC) Proceedings, 2017)
21st Century English Language Education is currently the focus and concern among English language practitioners and policy makers in ensuring success in all aspects of English Language endeavours. Since English language teaching is evolving in this rapidly changing world of education, numerous platforms are being used to discuss the latest developments pertaining to 21st Century Pedagogical Skills in English language education. As we move forward, this conceptual framework is being deliberated from various perspectives and levels to ensure that the outcome of any classroom practice should be significantly reflecting the principles of teaching and learning being advocated. Therefore, in enhancing pedagogical skills among practitioners of English language education, innovations and best practices will be the subject of discussions in trying to find the right formula for effective teaching and learning of English language aligned to the 21st Century educational framework.This presentation aims to revisit idealism and realism in enhancing pedagogical skills in English language teaching and learning, in accordance to the notion of 21st Century education conceptual framework. Other pertinent issues related to 21st Century pedagogical skills in English language education will also be discussed with the hope of finding common grounds in enhancing contextualized English language teaching.